Postoptimal analysis in the coefficients matrix of piecewise linear fractional programming problems with non-degenerate optimal solution - Behrouz Kheirfam (Opuscula Mathematica, 2010)
In this paper, we discuss how changes in the coefficients matrix of piecewise linear fractional programming problems affect the non-degenerate optimal solution. We consider separate cases when changes occur in the coefficients of the basic and non-basic variables and derive bounds for each perturbation, while the optimal solution is invariant. We explain that this analysis is a generalization of the sensitivity analysis for \(LP\), \(LFP\) and \(PLP\). Finally, the results are described by some numerical examples.